Implementasi Reward pegawai sebagai motivasi pada kinerja pegawai di (Balai Besar Penyaluran Penjamin Mutu Pendidikan Vokasi Bidang Bangunan dan Listrik) BBPPMPV BBL - Asbullah Harahap; Waizul Qarni (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
BBPMPPV BBL Medan has the main task and function of Facilitating the Improvement and Development of Educator Competencies. If the existing human resource managers are incompetent, lack work performance, and are not disciplined in time, the development of educator competence will definitely not match the expectations of the nation's future and worse. This type of research uses descriptive qualitative research. This study uses a qualitative type of research that is not through statistical procedures or other forms of calculation and seeks to understand and interpret certain situations from the researcher's own point of view. BBPPPMPV BBL Medan gives rewards to employees in the form of certificates of appreciation as a reward for the best work discipline and commitment, thus recruiting and retaining skilled, skilled, disciplined employees will continue to be motivated to continue to contribute to providing the best in completing their work. Keywords: Reward, Motivation, and Performance